Hysteria and its deceptive masks - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2022)
Hysteria still exists, even if this stigmatizing term has been abandoned in favor of more descriptive terms (dissociative disorders, conversion disorders, functional disorders), and represents a frequent and disabling pathology. Even if in some situations, the establishment of a definitive diagnosis remains difficult, more and more clinical and paraclinical signs are developing to help in the diagnosis and the error rate is low. Thus, the clinician must currently make a positive diagnosis of conversion and no longer, as unfortunately often in the past, confine himself to evoking by default such a possibility in the face of an atypical picture accompanied by an extensive negative paraclinical assessment. The most probable etiology concerns triggering factors of a psychiatric nature (traumatic episode or psychic stress, vulnerability with a field of abuse in childhood, comorbidity of anxio-depressive disorders), which can, in turn, lead to changes in brain function, the exact neurobiological correlate of which remains to be determined, even if many leads have recently been suggested by brain imaging. The care of these patients requires an in-depth and specialized examination, if possible, with the help of a neurologist, then psychiatric care, combined with somatic follow-up. In the future, a better understanding of the etiological mechanisms will make it possible to develop more specific treatments.